Effects of an actual insulin injection demonstration on insulin acceptance among patients with T2DM: a pragmatic randomized controlled trial - Choomai Atthayaporn; Wattanapisit Apichai; Tiangtam Orathai (Sciendo, 2021)
Introduction. Insulin injection refusal is a challenge when initiating insulin therapy. This study aimed to investigate the effects of an actual insulin injection demonstration on insulin acceptance in patients with type 2 diabetes mellitus (T2DM).